Using the IUCN Environmental Impact Classification for Alien Taxa to inform decision-making - Kumschick, Sabrina; Bertolino, Sandro; Blackburn, Tim M; Brundu, Giuseppe; Costello, Katie E; de Groot, Maarten; Evans, Thomas; Gallardo, Belinda; Genovesi, Piero; Govender, Tanushri; Jeschke, Jonathan M; Lapin, Katharina; et al. (Conservation biology, 2024)
The Environmental Impact Classification for Alien Taxa (EICAT) is an important tool for biological invasion policy and management and has been adopted as an International Union for Conservation of Nature (IUCN) standard to measure the severity of environmental impacts caused by organisms living outside their native ranges. EICAT has already been incorporated into some national and local decision-making procedures, making it a particularly relevant resource for addressing the impact of non-native species. Recently, some of the underlying conceptual principles of EICAT, particularly those related to the use of the precautionary approach, have been challenged. Although still relatively new, guidelines for the application and interpretation of EICAT will be periodically revisited by the IUCN community, based on scientific evidence, to improve the process. Some of the criticisms recently raised are based on subjectively selected assumptions that cannot be generalized and may harm global efforts to manage biological invasions. EICAT adopts a precautionary principle by considering a species' impact history elsewhere because some taxa have traits that can make them inherently more harmful. Furthermore, non-native species are often important drivers of biodiversity loss even in the presence of other pressures. Ignoring the precautionary principle when tackling the impacts of non-native species has led to devastating consequences for human well-being, biodiversity, and ecosystems, as well as poor management outcomes, and thus to significant economic costs. EICAT is a relevant tool because it supports prioritization and management of non-native species and meeting and monitoring progress toward the Kunming-Montreal Global Biodiversity Framework (GBF) Target 6.
Keywords: 影响评估; lidé; manejo de especies invasoras; evidence synthesis; precautionary principle; invasión biológica; 管理入侵物种; zachování přírodních zdrojů; evaluación de impacto; síntesis de evidencias; Ecosystem; principio de precaución; Humans; zavlečené druhy; 预防性原则; Conservation of Natural Resources; 证据整合; ekosystém; biodiverzita; 生物入侵; managing invasive species; Introduced Species; biological invasions; impact assessment; Biodiversity